A Systematic Literature Review: Analysis of Cost Control Methods on Inventory (Case Study in Indonesia) - Asri Usman; Mediaty; Mutiara Nur Qalbi; Nurul Latifah Nurdin; Elfina Damayanti (International Journal Of Economics Social And Technology, 2023)
The purpose of this study is to determine and analyze the methods used in the industry related to the management of their inventory to minimize inventory costs due to inventory mismanagement which can harm the company and the costs do not provide added value to the product. There are several methods that we analyze including Just In Time, Economic Order Quantity, Safety Stock, Reorder Point, Period Order Quantity, Material Requirement Planning, Min and Max, and Weight Moving Average we compare among all the existing methods, which one is the most widely used in the industry, this research uses the Systematic Literature Review method of journals stored on Google Scholar, with the period 2017-2023 based on case studies in Indonesia. This study found that the most widely used methods are EOQ and JIT, these two methods are used to adjust the needs and types of inventory owned by the company.